Human papillomavirus vaccine effectiveness within a cervical cancer screening programme: cohort study. (10th August 2020) - Acuti Martellucci, C; Nomura, S; Yoneoka, D; Ueda, P; Brotherton, JML; Canfell, K; Palmer, M; Manzoli, L; Giorgi Rossi, P; De Togni, A; Palmonari, C; Califano, A; et al.
Abstract : Objective: To assess the effectiveness of an HPV vaccination programme in reducing the risk of cervical abnormalities identified at subsequent screening. Design: Retrospective cohort study using administrative health data. Setting: General population of Ferrara Province, Italy. Population: Female residents born in 1986–1993 and participating in the organized cervical screening programme in 2011–2018, who were eligible for HPV vaccination in catch‐up cohorts. Methods: Logistic regression to evaluate the potential association between abnormal cervical cytology and one, two, three or at least one dose of HPV vaccine. Main outcome measures: Cervical abnormalities, as predicted by low‐grade or high‐grade cytology, by number of vaccine doses, stratified by age. Results: The sample consisted of 7785 women (mean age 27.5 years, SD 2.3). Overall, 391 (5.0%) were vaccinated with ≥1 dose and 893 (11.5%) had abnormal cytology. Women receiving at least one vaccine dose were significantly less likely to have an abnormal cytology (adjusted odds ratio 0.52; 95% confidence interval 0.34–0.79). Similar results were observed for women receiving a single dose, for both bivalent and quadrivalent vaccines, and applying buffer periods (excluding cytological outcomes within 1 month, 6 months and 1 year of the first dose). Conclusions: In the context of an organised cervical screening programme in Italy, catch‐up HPV vaccination almost halved the risk of cytological abnormalities. Tweetable abstract: Among Ferrara women, vaccination against human papillomavirus halved the risk of screening cervical abnormalities. Tweetable abstract: Among Ferrara women, vaccination against human papillomavirus halved the risk of screening cervical abnormalities.